Antiretroviral adherence and treatment outcomes among adult Ethiopian patients. Issue 8 (2nd August 2016) - Bezabhe, Woldesellassie M.; Chalmers, Leanne; Bereznicki, Luke R.; Gee, Peter; Peterson, Gregory M.
ABSTRACT: Developing appropriate strategies to sustain optimal medication adherence among the increasing number of HIV-positive patients taking antiretroviral therapy (ART) in sub-Saharan Africa is a major challenge. The objective of this study was to determine patient, regimen, disease, patient-provider, and healthcare-related factors associated with adherence with ART over a one-year period, and assess the impact of adherence on treatment outcomes. We performed a prospective, observational study among 246 patients who were initiated on ART in Ethiopia. Of 172 who completed follow-up, 130 (75.6%) had ≥95% adherence. In the multivariate analyses, a higher baseline BMI (OR, 1.2; 95% CI 1.0, 1.4) and use of reminder devices (OR, 9.1; 95% CI 2.0, 41.6) remained positively associated with adherence, while a higher HIV symptom and adverse drug reaction distress score was an independent negative predictor of adherence (OR, 0.90; 95% CI 0.9, 1.0) CD4 count increase was significantly higher in the adherent patients compared to non-adherent patients at 12 months (159 cells/µL [interquartile range (IQR), 72–324 cells/µL] vs. 132 cells/µL [IQR, 43–190 cells/µL]; p = 0.026). Our findings indicate that interventions aimed at improving adherence and thereby treatment outcomes in patients initiated on ART should promote the use of reminder devices, and monitor HIV symptoms and adverse reaction distress and nutritional status.